Kissing cousins: a review of the African genus Limnophis Günther, 1865 (Colubridae: Natricinae), with the description of a new species from north-eastern Angola. Issue 1 (31st August 2020) - Conradie, Werner; Deepak, V; Keates, Chad; Gower, David J
ABSTRACT: The African natricine genus Limnophis is represented by two species: Limnophis bicolor Günther, 1865 and Limnophis bangweolicus (Mertens, 1936 ). They are stout-bodied, semi-aquatic snakes that mostly feed on fish and amphibians, and occur from Botswana and Namibia in the south throughout most of Zambia and Angola to the Democratic Republic of the Congo in the north. We gathered new material from the ranges of both species in Angola and Zambia in order to examine their taxonomic status and identify any overlooked diversity. We constructed a phylogenetic tree, based on three mitochondrial genes ( 16S, cytb, ND4 ) and one nuclear gene ( cmos ), which includes the first DNA sequence data for Limnophis . Three well-supported lineages were identified, each representing separate species. The taxonomic status of the two currently recognised species is validated, and we describe a new species of Limnophis from north-eastern Angola. The new species is distinguished from the others by the combination of distinct ventral and lateral head colouration and patterning, differences in head and ventral scalation, and uncorrected pairwise genetic distances to both L. bicolor and L. bangweolicus of 5.4–8.1% in cytb, 6.1–8.4% in ND4 and 2.7–8.3% in 16S .